Board governance on dividend initiation by initial public offerings: Evidence from the Malaysian Stock Market - Nizar Dwaikat; Abdelbaset Queiri; Ihab Sameer Qubbaj (Cogent Economics & Finance, 2020)
Within the realm of corporate finance, IPO (refers to the process of offering shares of corporation to the public for the first time) companies in Malaysia received little attention from the academic scholarly works. An important area of inquiry for IPO companies is to investigate the board characteristics impact on dividend initiation. With use of the agency theory principles, four argumentative hypotheses were proposed. The current study used a pooled cross-sectional data with a total sample size of 372 companies listed in the Malaysian Stock Market. The results of this study revealed that the independence of board and the size of board were found to have a positive and significant impact on the decision to initiate dividend for IPO companies. However, multi-seats were found to have a negative and significant impact on the decision to initiate dividend. But, CEO duality were found to be irrelevant to the decision of initiating dividend.
Keywords: G3; G35; G41; 330; Agency theory; board characteristics; dividend initiation; Malaysian stock market; IPO companies